Person-centered care for dementia patients (frontend and backend development) - Ma, Xinyi (Nanyang Technological University, 2024)
Dementia poses a significant global challenge, affecting millions of individuals, and placing considerable strain on healthcare systems and caregivers worldwide. This final year project explores the development and refinement efforts within the Person-Centered Care (PEAR) system, which aims to cater to the diverse needs of dementia patients and their caregivers. It details the implementation of PEAR across web and mobile platforms, highlighting its crucial role in simplifying caregiving responsibilities and empowering healthcare professionals. The report offers insights into the web application development process, emphasizing the use of design patterns and rigorous testing methodologies to ensure the system's resilience and user-friendliness. Collaborative efforts with the scheduler team are focused on integrating APIs and webpages to enhance scheduling processes within the PEAR system. Additionally, working closely with the mobile development team involves adjusting or introducing APIs according to their specific needs. This integration aims to facilitate seamless communication between platforms, thereby enhancing the user experience and promoting system cohesion. Meanwhile, identified bugs, validated through testing by the project supervisor, are meticulously addressed to fortify the platform's stability and reliability. Meanwhile, tasks related to database management are undertaken to ensure efficient data storage and retrieval, maintaining the integrity and reliability of the system's data. Moving forward, future work entails the continuous resolution of existing bugs in the web application and the addition or enhancement of features to align with evolving requirements. This ensures the ongoing enhancement and adaptability of the PEAR system, reinforcing its effectiveness in addressing the needs of dementia patients and caregivers.